2018
DOI: 10.5713/ajas.17.0419
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and divergence among Korean cattle breeds assessed using a BovineHD single-nucleotide polymorphism chip

Abstract: ObjectiveIn Korea, there are three main cattle breeds, which are distinguished by coat color: Brown Hanwoo (BH), Brindle Hanwoo (BRH), and Jeju Black (JB). In this study, we sought to compare the genetic diversity and divergence among there Korean cattle breeds using a BovineHD chip genotyping array.MethodsSample data were collected from 168 cattle in three populations of BH (48 cattle), BRH (96 cattle), and JB (24 cattle). The single-nucleotide polymorphism (SNP) genotyping was performed using the Illumina Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
5
12
1
Order By: Relevance
“…As the MAF values range was comparable among the studied breeds, our results might suggest similar variability of the breeds, which was also confirmed by the similar expected heterozygosity across the breeds. The degree of polymorphism observed in the present study was similar to that reported by Li and others (Li et al, 2019) for Chinese cattle breeds (89.9%) and by Cañas-Álvarez and others (Cañas-Álvarez et al, 2015) for Span-ish breeds (86-98%), however, it was higher than previously reported for Korean cattle, where the proportion of SNPs with MAF>0.05 ranged between 72.7% and 76.16% (Kim et al, 2018). On the other hand, according to Zhang and others (Zhang et al, 2018), the percentage of SNPs observed in twenty Chinese indigenous cattle breeds was quite varied: between 72.9% and 97.2%.…”
Section: Resultssupporting
confidence: 91%
“…As the MAF values range was comparable among the studied breeds, our results might suggest similar variability of the breeds, which was also confirmed by the similar expected heterozygosity across the breeds. The degree of polymorphism observed in the present study was similar to that reported by Li and others (Li et al, 2019) for Chinese cattle breeds (89.9%) and by Cañas-Álvarez and others (Cañas-Álvarez et al, 2015) for Span-ish breeds (86-98%), however, it was higher than previously reported for Korean cattle, where the proportion of SNPs with MAF>0.05 ranged between 72.7% and 76.16% (Kim et al, 2018). On the other hand, according to Zhang and others (Zhang et al, 2018), the percentage of SNPs observed in twenty Chinese indigenous cattle breeds was quite varied: between 72.9% and 97.2%.…”
Section: Resultssupporting
confidence: 91%
“…These smaller N e values obtained from Heugu are in concurrent with the estimated lower within-breed genetic diversity. The N e values obtained in this study for the last 13 generations are far lower than those reported for Hanwoo (260) and Chikso (202) [17], but higher than the values estimated for Hanwoo (83) and Chikso (59) [18]. This difference can be attributed to the difference in genotyping arrays, Bovine HD and SNP50, respectively.…”
Section: Linkage Disequilibrium and Demographic Historycontrasting
confidence: 80%
“…Specifically, the Korean black (Heugu) cattle retained the lowest level of within-breed genetic variation (Table 1). The observed heterozygosity in Han- woo and Chikso are higher than the values (0.26-0.29) estimates from high-density SNPs [17], but far lower than the microsatellite (0.67) [5] and Bovine SNP50 BeadChip based estimates (0.38-0.44) [18]. The low level of genetic variability obtained from Heugu is possibly attributed to genetic drift associated with low effective population and geographical isolation [4].…”
Section: Resultsmentioning
confidence: 60%
“…However, comparing our findings directly with previous reports is difficult because of differences in the scale of sampling, given that the level of LD decreases with increasing sample size [ 69 ]. Recently, the pattern of LD decay was reported in various cattle and buffalo breeds across the world, including an Iranian water buffalo population at an average of 57 kb decay [ 70 ], Chinese buffalo breeds at 50 kb for the river group and 15 kb for the swamp group [ 49 ], Tunisian cattle at 73.4 kb [ 71 ], Korean cattle breeds from 26 to 32 kb [ 72 ] and Colombian Creole cattle breeds from 70 to 100 kb [ 73 ].…”
Section: Discussionmentioning
confidence: 99%